THE SUPERIORITY OF ONLINE TEACHING FOR ECONOMICS STUDENTS - Sohiba Ruzmetova (Bright Mind Publishing, 2025)
Online teaching has revolutionized the educational landscape, offering unparalleled advantages for economics students. This study explores the effectiveness of online teaching in economics, emphasizing its superiority over traditional methods. The research highlights benefits such as flexibility, resource availability, personalized learning, and enhanced accessibility. While challenges exist, such as maintaining engagement and assessment integrity, advancements in technology and instructional design have significantly mitigated these concerns. The findings suggest that a well-structured online education system provides a more efficient and inclusive learning environment for economics students. Additionally, statistical data and visual representations, including charts and diagrams, illustrate key trends supporting the effectiveness of online teaching.
Keywords: Online Teaching, Economics Education, Student Engagement, Digital Learning, Adaptive Learning Technologies.